How GCG, Profitability, Firm Size, Leverage Affect the Value Company of IDX-Listed Consumer Products Companies? - Vivin Gotama Tie; Retno Indah Hernawati (Jurnal Telekomunikasi dan Informatika, 2025)
This research is aimed at analyzing the effect of institutional ownership, profitability, firm size, and leverage on firm value in the consumer products sector-the period of listed on the IDX during 2015-2024. The type of research conducted here is quantitative. The data analysis used in this study is multivariate linear regression analysis. The sampling used in this research is purposive sampling, where a sample of 50 firms was taken for re-testing outlier identification purposes. Based on the results of the multiple linear regression tests, it could be seen that, though institutional ownership did not affect significantly the value of the firm, profitability proxied by ROE bore a positive and significant impact, showing that the capability to generate profit from equity was one of the needed capabilities of a firm-a crucial aspect which may draw the attention of investors. Firm size made a negative signif-icant impact, while its leverage had a negative and significant relationship, showing that the market looked at increasing debt as a financial risk instead of evidence of growth. These findings support the view that profitability and financial stability are the chief determinants of company value within Indo-nesia's consumer products industry.